Role of topical phenytoin in treatment of chronic venous ulcers - Singh, Santosh Kumar; Lata, Sneh; Gupta, Anil Kumar; ., Rajkumar (International Journal of Research in Dermatology, 2020)
Background: Venous leg ulcers are a common cause of significant morbidity leading to compromised quality of life and a huge financial burden on patients. Apart from the systemic therapy, many topical agents are available to accelerate healing in these ulcers. Topical phenytoin is one such agent which has been studied for promotion of wound healing. The aim of the study was to study the efficacy of topical phenytoin in healing of chronic venous ulcers. Methods: 56 patients of chronic venous ulcer were randomly divided in two groups of 28 each. First group was given daily dressing of phenytoin in normal saline (group A) and second group was given only normal saline dressing (group B) for a period of 8 weeks. After 8 weeks the reduction in size of ulcer was measured, on the basis of which results were calculated. Results: The mean age of the patients was 50.29±13.37 years. The mean duration of ulcer was 10.13±4.66 weeks. Compared to the conventional normal saline dressing, patients given phenytoin and normal saline dressing showed far greater tendency to heal (p=0.02). 35.7% patients in phenytoin group showed excellent response out of which 21.42% achieved complete healing, while in normal saline group only 14.28% patients showed excellent response and none of patient showed complete healing. No significant adverse effects were observed in either of the group. Conclusions: Topical phenytoin appears to be a safe, easy, effective and inexpensive option to promote wound healing and can be used as an adjuvant for treatment of chronic venous ulcers. Further studies with larger population are merited.